2023
DOI: 10.47738/ijaim.v3i3.58
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of an "Internet+" Grounded Approach for Establishing a Model for Evaluating Financial Management Risks in Enterprises

Hongli Wang

Abstract: With the rapid development and continuous updating of computing technology, computer software is increasingly used in various management of enterprises, which brings great aspects to enterprise management and also creates high benefits for enterprises. This article takes the hospital as an example, based on Internet technology, evaluates the risks of the hospital financial management system, and establishes the relevant risk evaluation model according to the relevant elements of the medical financial managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that risk control with the ISO 27002:2013 code of practice for information security controls can increase the cyber maturity value of an organization from a maturity value of 3.19 to 4.06 by implementing 12 new security controls. At maturity level 4, the organization ensures that cyber security management is managed, regulated, regularly reviewed, and continuous [12] [13]. Research in Rembang Regency provides recommendations for risk mitigation efforts on 13 ISO 27001 controls based on equivalent risk analysis [14] [15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that risk control with the ISO 27002:2013 code of practice for information security controls can increase the cyber maturity value of an organization from a maturity value of 3.19 to 4.06 by implementing 12 new security controls. At maturity level 4, the organization ensures that cyber security management is managed, regulated, regularly reviewed, and continuous [12] [13]. Research in Rembang Regency provides recommendations for risk mitigation efforts on 13 ISO 27001 controls based on equivalent risk analysis [14] [15].…”
Section: Introductionmentioning
confidence: 99%